Perancangan Aplikasi E-surat Berbasis Mobile pada Pemerintahan Desa Kedunggede Kecamatan Lumbir - Gustin Setyaningsih (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Information technology is experiencing rapid development in various fields such as education, health, banking, government and other fields. The rapid development of information technology affects administrative procedures in government. Therefore, government administration procedures must be able to adapt by applying information technology in all aspects of government. One of the government administrative procedures is the management of documents. In dealing with letters such as cover letters, the community must bring a cover letter from the head of the RT and the local RW head then to the Kedunggede Village Office by bringing the requirements according to the provisions and waiting in line with other communities. If the required documents are incomplete, the community must return home to complete the file, then return to the Kedunggede Village Office. This is inefficient and will increase the queue at the Kedunggede Village Office. Especially in the current state of the COVID-19 pandemic, the government urges people to keep their distance and not to gather together. So, a mobile-based e-Surat application was made at the Kedunggede Village Office to solve this problem. This study uses the waterfall method which has a systematic software lifeflow approach. With this e-Surat application, the people of Kedunggede Village can submit letters anytime, anywhere without having to leave the house and queue at the Village Office so as to reduce the possibility of crowds forming at the village office to reduce the risk of increasing Coronavirus Disease (Covid-19).